Implementation of the "7 poe atika" program for instilling student character values in schools - Aulia Riski; Rino Rino; Diding Nurdin; Nani Hartini (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2023)
This study aims to obtain information on how to implement and cultivate the character values of the 7 Poe Atikan implemented in the Purwakarta district. This study took data using a qualitative approach with descriptive methods. The collection techniques are observation, interviews, and literature study as data collection techniques. This research was conducted at SDN 2 Munjuljaya Purwakarta. The results of this study obtained information regarding the cultivation of character values from the 7 P oe Atikan Istimewa which were implemented at SDN 2 Munjuljaya Purwakarta which had been implemented and instilled character values in students through several different activities every day. This research implies that the implementation of the 7 Poe Atika in schools can instill character values in students to improve the abilities and quality of students at school and outside of school.